Asthma severity and fertility outcome in women with polycystic ovary syndrome: a registry-based study - Louise Zierau; Rikke Cortes; Simon Francis Thomsen; Espen Jimenez-Solem; Svend Lindenberg; Vibeke Backer (ERJ Open Research, 2018)
Recent research suggests that women with polycystic ovary syndrome (PCOS) have a higher risk of asthma. However, the severity of asthma, use of antiasthma medication and effect on fertility have yet to be investigated. In a case–control cross-sectional registry study using the Danish National Patient Register and other Danish registries, asthma prevalence, asthma severity, antiasthma medication use and fertility outcome were investigated among two groups of women with PCOS (n=1358 and n=17 123) and a healthy control group (n=5340). Both asthma prevalence (OR 1.45, 95% CI 1.24–1.70) and mean daily inhaled corticosteroid dose were higher among women with PCOS compared with healthy controls, whereas asthma severity was the same in women with and without PCOS. Women with PCOS and asthma had more in vitro fertilisation treatments than women in the control group with asthma, but the numbers of children per woman and spontaneous abortions were the same. Women with PCOS have a higher prevalence of asthma and a higher use of inhaled corticosteroids, whereas asthma severity is the same in women with and without PCOS. Asthma is associated with more in vitro fertilisation treatments in women with PCOS.